Investigation of Dental Implants Operated in Private Dental Office: Cross-Sectional Study - Özgün Yıldırım; Süleyman Demirağ (European Annals of Dental Sciences)

(untitled)
Purpose: The aim of this study is to analyze the demographic characteristics of patients who underwent dental implant surgery and various features of the implants applied, in a private clinic from January 2019 to June 2022 in Turkey by descriptive methods. Materials & Methods: The files of the patients who were operated analyzed. Gender, age, edentulous status, implant brands used and various characteristics of the patients were recorded. The obtained data were evaluated with descriptive statistical analysis.Results: Total of 90 patients, 39 (43.34%) male and 51 (56.66%) female, were included in the study. When analyzed by decades, it was determined that the most treated range was 39-48 years with 27 (30%) patients. Of the 247 implants applied, 139 (56.27%) were placed on the right side (1st and 4th regions), and 108 (43.72%) were placed on the left side (2nd and 3rd regions). When examined according to the jaws they were applied to, 137 (55.46%) of them were applied to the mandible and 110 (44.53) of them were applied to the maxilla. Of these implants, 44 (17.81%) are in the anterior position (incisors and canine teeth region), and 203 (82.18%) are in the posterior position (1st premolar and beyond). Conclusion: Dental implants can be easily applied to every individual in line with the appropriate indication. The findings in this article will help operators to choose the suitable indication.